Estudo da molhabilidade de vidrado composto de resíduo de rochas ornamentais em cerâmica vermelha - Carvalho, Romário Alves (2017)
The dimension stone industry generates large amounts of solid waste and an alternative to reduce this environmental liability is its use in the production of glazes. The objective of this work was to study the wettability of glaze made of dimension stone waste in red ceramic using the method of Sessile Drop. Six glaze compositions were prepared containing 49 to 77% of residue. The glaze was pressed with dimensions of 3mm x 3mm x 3mm and placed on a sintered red ceramic plate, and both were heated to fusion of the glaze up to temperature of 1100ºC. The variation of the contact angle was measured as a function of temperature, and the tests were repeated in specific isotherms to evaluate the kinetics of transformation. The contact angles from 1100°C change between 9 – 98° depending on the composition, indicating some glaze wet the surface of the ceramic satisfactorily while others do not spread, and therefore would not be indicated as composition for coating ceramic. The interface between the glaze and red ceramic showed physical interaction, indicating no reaction layer between the constituents.